Contact dermatitis due to personal protective equipment use and hygiene practices during the COVID-19 pandemic: A systematic review of case reports. (February 2022) - Sarfraz, Zouina; Sarfraz, Azza; Sarfraz, Muzna; Felix, Miguel; Bernstein, Jonathan A.; Fonacier, Luz; Cherrez-Ojeda, Ivan
Abstract: Background: Prolonged use of personal protective equipment (PPE) may lead to contact dermatitis during the coronavirus disease 19 (COVID-19) pandemic. This paper aims to identify the causative factors of contact dermatitis from PPE and hygiene practices. Methods: The search was conducted adhering to PRISMA 2020 guidelines. A Delphi process was employed to ensure that the aims of this study were met. PubMed and Web of Science databases were systematically searched through September 12, 2021, using search terms: Contact dermatitis, case report, covid-19. The findings were tabulated as author/year, gender, age, presentation, cause, dermatological diagnosis, testing modality, provided treatment, symptom resolution (time in days), prognosis, and follow-up. Results: The mean age of all individuals was 29.75 years, with 75% females. All cases presented with erythema, with 62.5% reporting pruritus and 37.5% reporting burning facial symptoms. Surgical masks and hand-hygiene products (37.5%) were the most commonly reported causative agent with 25% due to KN95/FFP type 2 use. Allergic contact dermatitis (50%) and irritant contact dermatitis (25%) were common diagnoses. Treatments included creams, emollients, and desloratadine, with restriction of irritant-causing factors. The prognosis was generally good among the cases, with 62.5% presenting complete resolution within a week and 12.5% showing moderate improvement at the fourth month after discontinuing use. Conclusion: This study finds pertinent links between PPE use and contact dermatitis during the COVID-19 pandemic. While many cases are bound to go underreported in literature, well-designed, large-scale studies in the future may help promote these associations in a more comprehensive manner. Highlights: Prolonged PPE use for COVID-19 makes users vulnerable to contact dermatitis. Irritant and contact dermatitis due to surgical masks/KN95/FFP type 2/hygiene products was reported. Treatments include creams, emollients, desloratadine and avoidance of irritants.